Stuffed and Preserved: The Paradox of Overeating in Seneca’s Epistulae Morales - Santucci, Robert (Lucius Annaeus Seneca, 2024)
This article argues that the Epistulae Morales dramatizes overeating as a problem that Seneca develops throughout the letters. The overeater stuffs their belly with food, dies, and finally becomes a sort of food. This progression signals that issues of food and eating thus bear on Roman social commitments in addition to their expected philosophical significance, since in the pursuit of stuffing the belly the overeater reneges on their social obligations.